Elements of literature : fourth course with readings in world literature - Robert E. Probst (Austin : Holt, Rinehart and Winston, Inc., 2000)
There are only two or three human stories, and they go on repeating themselves as fiercely as if they had never happened before. -- Willa Cather
Collection1. Hard Choices -- Collection2. Hearts that Love -- Collection3. Exiles, Castaways and Strangers -- Collection4. Breakthroughs -- Collection5. Becoming Myself -- Collection6. Being There! -- Collection7. Making a Point -- Collection8. How to Live -- Collection9. Can This Be Love? -- Collection10. Dreams- Lost and Found -- Collection11. Doing the Right Thing -- Collection12. Ambition or Honor -- Collection13. Sources of wisdom -- Collection14. finding our Heroes .
Includes index.
Keywords: LITERATURE